Lower Extremity Venous Doppler Evaluation in Patients Undergoing Laparoscopic Gynecological Operations - Kumbak, Banu; Poyraz, Ahmet Kursad; Baspinar, Melike; Sahin, Levent; Ozkan, Zehra Sema (Mary Ann Liebert, Inc, 2013)
Background: Laparoscopy is established as a standard of care in a variety of gynecological pathologies. Pneumoperitoneum and reverse Trendelenburg positioning during laparoscopy have been claimed to increase thrombosis risk, albeit these proposals are still controversial. The aim of this study was to assess lower extremity venous blood flow by Doppler sonography in patients undergoing laparoscopic gynecological surgeries. Patients and Methods: A prospective, nonrandomized, controlled study was designed to compare lower extremity venous Doppler measurements in patients undergoing diagnostic and operative gynecological laparoscopies. In the period from May 2010 to April 2011, in total, 96 patients operated on for various gynecological complaints excluding malignancy were enrolled in the study. Thirty-two of these patients underwent diagnostic laparoscopy, 34 underwent operative laparoscopy, and 30 underwent open surgery. Lower extremity venous blood flow was investigated by Doppler sonography in patients the day before surgery and 24 hours afterward. Preoperative and postoperative Doppler measurements were obtained from bilateral common and superficial femoral, bilateral great saphenous, and bilateral popliteal veins. Results: Lower extremity venous Doppler measurements were similar in diagnostic and operative laparoscopy groups. Femoral venous blood flow measurements were observed to be similar, but great saphenous and popliteal blood flows were found to be significantly decreased in the open surgery group compared with laparoscopic operations. Conclusions: The laparoscopic approach in gynecological surgery is not associated with an adverse effect on lower extremity blood flow and seems not to bring an additional risk of thrombosis.
Keywords: Pulmonary-Embolism; Cholecystectomy; Surgery; Thromboembolism; Thrombosis; Risk; Thrombophlebitis